THE EFFECTIVENESS OF ANNUAL PLANNING IN DEVELOPING STRENGTH AND SPEED-STRENGTH INDICATORS OF YOUNG SHORT-DISTANCE RUNNERS - J.N. Eshpulatov (International Journal of Literature and Language Studies, 2026)
This article analyzes the scientific and theoretical foundations of annual planning in the development of strength and speed-strength qualities in young short-distance runners. Achieving high results in sprint events directly depends on the athlete’s explosive strength, reactive power, and maximum speed abilities. Therefore, the scientific distribution of training loads throughout the year is of great importance. The article discusses the principles of periodization in annual planning, the stages of developing strength and speed-strength qualities, and the physiological adaptation mechanisms of young athletes. The results of the study show that the gradual application of training loads and proper consideration of recovery processes lead to high training effectiveness.